Effectiveness of Human Resource Management Information System (HRMIS): A Case Study of Royal Army Engineers Regiment of Malaysia - Mohamad Hatta, Muhammad Azri; Mohd Noor, Nurul Hidayana (Journal of Technology Management and Business, 2025)
The use of computer-based information systems to help improve the performance of an organization can be seen in almost all management and administrative activities. A Human Resource Information System (HRIS) is used to obtain, store, manipulate, analyze, retrieve, and distribute important information about human resource activities in an organization. The Human Resource Management Information System (HRMIS) system is one example of an HRIS system. This study aims to identify the predictors of the effectiveness of the HRMIS system, namely performance expectancy, effort expectancy, attitudes toward technology, and social influence. This study used a questionnaire to collect data from 91 Royal Engineers Regiment Malaysian Army staff. A total of 291 respondents were involved in this study. The data are analyzed using Pearson correlation and multiple regression. This study's findings show a significant relationship between all variables and social influence, the most significant predictor of HRMIS effectiveness. The results support the combination model of the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Theory of Planned Behavior (TPB). In conclusion, a sound HRMIS system can catalyze organizational success.